METHODOLOGY FOR THE ANALYSIS OF THE OPERATION OF HIGH-PERFORMANCE COMPUTING EQUIPMENT - AUCCAHUASI, WILVER (2024)
HIGH-PERFORMANCE COMPUTING EQUIPMENT USES GRAPHIC PROCESSORS, KNOWN AS GPUS, AS A MECHANISM FOR HIGH COMPUTATIONAL CAPACITY. TO INCREASE THE COMPUTATIONAL CAPACITY, ADDITIONAL GRAPHICS PROCESSORS ARE ADDED IN THE CONFIGURATIONS. THIS STRATEGY INCREASES THE COMPUTATIONAL CAPACITY AS WELL AS CONSIDERABLY INCREASES THE TEMPERATURE GENERATED BY THE ENTIRE SYSTEM, NORMALLY THE GPUS HAVE COOLING SYSTEMS, WHICH HELP TO COOL AS MUCH AS THEY ARE REQUIRED, THE OPERATING SYSTEMS HAVE AUTOMATIC MECHANISMS TO ACCESS THE GPUS, THESE FUNCTIONS ARE ACTIVATED WHEN IT IS REQUIRED TO USE THEM, IN THE EVENT OF A NEED FOR HIGH COMPUTING CAPACITY REQUIREMENT. IN THIS WORK WE DEMONSTRATE A METHOD TO ANALYZE THE OPERATION OF COMPUTING EQUIPMENT WHEN WORKING ON HIGH-PERFORMANCE FUNCTIONS, SUCH AS VIDEO GAMES, WHICH REQUIRE HIGH COMPUTATIONAL CAPACITY TO BE ABLE TO PLAY IN REAL TIME AND PERFORM THE TASKS. NECESSARY RENDERINGS, THE METHOD CAN BE APPLIED TO OTHER APPLICATIONS THAT ARE NECESSARY TO ENSURE THE CONTINUED OPERATION OF THE COMPUTING EQUIPMENT. © 2024 TRANS TECH PUBLICATIONS LTD, SWITZERLAND.